DYNAMICITY OF INTERLANGUAGE ERRORS: A CASE STUDY OF INDONESIAN STUDENTS LEARNING ENGLISH AS A FOREIGN LANGUAGE - Endang Fauziati (Indonesian Journal of Applied Linguistics, 2011)
ABSTRACT: Interlanguage errors are an inevitable sign of human fallibility; therefore, they always exist in foreign language learning. They are very significant since they become the source for studying the system of the learners’ second language (interlanguage). As a language system, interlanguage has at least three prominent characteristics, namely, systematicity, permeability, and fossilization. Applied linguistic researchers are no longer in disagreement with the view that interlanguage is systematic and permeable. However, the premise that interlanguage is fossilized is still debatable. This study deals with interlanguage errors; in particular, this tries to investigate whether the learners’ grammatical errors are fossilized (in a sense that they are dynamic) or static. For this purpose, an empirical study was conducted, using an error treatment method. This study used Indonesian senior high school students learning English as the research subjects.